Impact of the Presence of Bunker of Liquid Organic Fertilizer (POC) on Groundwater for Drinking in Sambungmacan Sragen - Anna, Alif Noor; Suharjo, Suharjo; Kaeksi, Retno Woro (Forum Geografi, 2003)
The study of impact of the banker of liquid organic fertilizer (POC) on groundwater is carried out in Sambungmacan Sragen. The banker is made of concrete cement and it is located in the settlement area. This bunker causes obstruction for population, such as the smell bad, many died cassava, plants, and well pollution. The source of these obstruction is the leakage that permeates on groundwater used for drinking water. The aims of this study are know 1) the apportion of the groundwater pollution; 2) the level of groundwater pollution of drinking water. The result of the study shows that POC has permeated two populationâs wells that are located in radius eight meters. The water of wells is muddy and smells bad. Finally the well in north side of the banker is not used anymore, while the well in the west side of the banker, its water is still fresh after it has been drained twice. After the banker of liquid organic fertilizer (POC) is not be used anymore and the well which is polluted by POC has been drained, cause of that, the quality of groundwater in the research area generally still fullfills the requirement of drinking water, except the well in north side of the banker because it is polluted (the smell and color). So that, classification groundwater pollution in research area is still in very low level.